Training in Production of Liquid Organic Fertilizer from Various Vegetable Wastes in Nagari Panyalaian Kecamatan X Koto Kabupaten Tanah Datar - Melindra wanda Mulia (Pelita Eksakta, 2021)
Nagari Panyalaian Kecamatan X Koto Kabupaten Tanah Datar is a vegetable producing center in West Sumatera. It produces various type of vegetables. Sometimes, people could not maintain their own garden products because it costs more money than their profit. Therefore, this community service goal was to train the farmer or people in Nagari Panyalaian in making liquid organic fertilizer from their vegetable waste. Before this program started, the community of Nagari Panyalaian was motivated to join this program but their knowledge was still limited. In this program, they were trained in making liquid organic fertilizer from vegetables waste materials by using a simple way. After this program the people will have knowledge to maintain their own garden products as liquid organic fertilizer which is economically valuable.